Architectural and physical properties of fungus comb from subterranean termite Macrotermes gilvus (Isoptera: Termitidae) mound - Dina Kusumawardhani; Dodi Nandika; Lina Karlinasari; ARINANA ARINANA; IRMANIDA BATUBARA (Society for Indonesian Biodiversity, 2021)
Abstract. Kusumawardhani DT, Nandika D, Karlinasari L, Arinana, Batubara I. 2021. Architectural and physical properties of fungus comb from subterranean termite Macrotermes gilvus (Isoptera: Termitidae) mound. Biodiversitas 22: 1627-1634. Subterranean termite Macrotermes gilvus Hagen (Isoptera; Termitidae) is the most widely distributed termite species in Indonesia. This termite species has a unique habit of making fungus comb inside their nest. The fungus comb is a growth substrate for Termitomyces fungi, which provides a nutrient source for the termite. However, there is a lack of scientific information regarding the architecture and physical properties of fungus combs of M. gilvus. A study was conducted to determine the architecture and physical properties of fungus combs of M. gilvus found in Yanlappa Experimental Forest, Bogor, West Java Province, Indonesia. The fungus combs were collected from six of twenty-two nests of M. gilvus found in the rectangular sample plot (150 x 250 m) in the area. The results showed that the fungus comb of M. gilvus was brain-shaped with 44.17 ± 7.36 cm3 in volume and had burrows that interconnected from the surface (6.20 ± 1.06 mm in diameter) to the base of the fungus comb structure (4.32 ± 0.91 mm in diameter). The burrows were interconnected with each other to support cross-ventilation in the fungus comb. White nodules of Termitomyces fungi were found in the fungus comb. Architecturally, the fungus comb consisted of two structural parts, namely fresh comb on the upper part and old comb on the lower part of the fungus comb. The fresh comb possessed a larger volume (48.33 ± 2.89 cm3) and smoother texture (177.88-977.50 nm) than the old comb (40.00 ± 8.66 cm3, 407.49-6762.62 nm). The fresh comb had a larger volume (48.33 ± 2.89 cm3) than the old comb (40.00 ± 8.66 cm3). It was also found a smoother texture in the fresh comb (177.88-977.50 nm) than in the old comb (407.49-6762.62 nm). In terms of color, the fresh comb was darker (reddish) than the old comb (yellowish white). In addition, the density of the old comb was higher (0.87 ± 0.11 g/cm3) than the fresh comb (0.77 ± 0.13 g/cm3) so that the old comb was able to function as a strong foundation for fungus comb.